Trends in reactivity of electrodeposited 3d transition metals on gold revealed by operando soft x-ray absorption spectroscopy during water splitting. (2nd December 2016) - Velasco-Vélez, J J; Jones, Travis E; Pfeifer, Verena; Dong, Chung-Li; Chen, Yu-Xun; Chen, Chieh-Ming; Chen, Hsin-Yu; Lu, Ying-Rui; Chen, Jin-Ming; Schlögl, R; Knop-Gericke, A; Chuang, C-H
Abstract: We activated gold electrodes for their use as electrocatalyst for water splitting by electrodepositing Cu, Ni and Co. A combination of operando x-ray absorption spectroscopy and potentiometric control under aqueous conditions revealed the trends in reactivity yielded by these electrodes, which are directly associated with the cross- and overpotentials as well as the occupancy of the 3d orbitals. It was found that under anodic polarization the materials electrodeposited on gold suffer from a lack of stability, while under cathodic polarization they exhibit stable behavior. The observed activity is strongly related to the lack of stability shown by these composites under anodic polarization revealing a dynamic process ruled by corrosion. By operando x-ray absorption, we established that the overall enhancement of the activity for the oxygen evolution reaction is directly attributable to the cross-potential and corrosion process of the electrodeposited materials. It is associated with the high potential deposition, which is the origin of the incipient oxidation-corrosion resistance of the lattice. We conclude that the observed trends in the total current are directly associated with the loss of oxygen in the metal-oxide lattice and the subsequent dissolution of metallic ions in the electrolyte under anodic polarization.